Optimization of Yards and Vacant Land in Pajangan Hamlet, Wedomartani, Yogyakarta as a Living Pharmacy and Food Garden - Yuvita, Arneta; Utami, Zidni Meirizka; Rahayu, Fadiah Sri; Wardani, Ester Dewanti Yovita; Artik, Arba' Ramadhani; Nuriliani, Ardaning (Transformatif : Jurnal Pengabdian Masyarakat, 2025)
This community service program aimed to maximize vacant land and home yards in Pajangan Hamlet, Sleman, Yogyakarta by building living pharmacies and food garden. Using the Asset-Based Community Development (ABCD) approach, the initiative concentrated on locating and organizing local resources to raise sustainable living and health literacy. Activities including pre- and post-intervention assessment, educational workshops, and building of demonstration gardens out of recycled materials. This program successfully increased residents’ understanding of degenerative diseases and encouraged the use of medicinal plants and organic food. It also promoted home gardening and composting, supporting food security and lessening dependency on synthetic medications. These results show the possibilities of inexpensive, neighborhood-based healthcare projects.